Inactivation of Zika Virus with Hydroxypropyl-Beta-Cyclodextrin - Cory R. Hewitt; Nicholas J. Wixon; Arthur Gallegos; You Zhou; Victor C. Huber; M. Scott Killian (Vaccines)
Background/Objectives: Zika virus (ZIKV) infection is associated with life-threatening diseases in humans. To date, there are no available FDA-approved therapies or vaccines for the specific treatment or prevention of ZIKV infection. Variation in the ZIKV envelope protein (Env), along with its complex quaternary structure, presents challenges to synthetic approaches for developing an effective vaccine and broadly neutralizing antibodies (bnAbs). We hypothesized that beta-cyclodextrin (BCD) could be used to uniquely inactivate infectious ZIKV without disruption of Env. Methods: ZIKV was propagated in Vero cells and admixed with BCD. The BCD-treated ZIKV was evaluated for infectivity using immunofluorescence and quantitative RT-PCR (qRT-PCR) assays, for immunoreactivity in Western blots, structural integrity by electron microscopy, and immunogenicity in mice. Results: Here, we show that 200 mM BCD-treated ZIKV is non-infectious in cell culture, remains immunoreactive with an Env-specific antibody, retains its virion shape and size, and elicits the production of immunogen-specific antibodies in immunized mice. Conclusions: These results indicate that BCD can be used to safely inactivate ZIKV, and they provide insights for vaccine and antibody development.